ANALISIS KEMASLAHATAN PENGGUNAAN LIMBAH DI INDUSTRI SEMEN DALAM PERSPEKTIF SYARIAH ISLAM - Susanto, Yayan; Chaniago, Asdi; Misno (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2024)
This study aims to analyze the benefit value of the use of waste in the cement industry, which is currently widely used in almost all cement industries in Indonesia from the point of view of Islamic sharia. This is considered and seen accompanied by supported data from observations and research that the waste used is consumable materials or leftovers from other materials that are no longer used which tend to decrease or even have no benefits or even harm, but can be utilized again as raw materials and fuel. However, in the end, after experiencing the production process of mixing and heating, these wastes will become building materials that will interact directly with users as a new material called cement This study conducted a review and analysis of the benefit value from the perspective of Islamic sharia on the consideration that waste is a material whose constituent ingredients are not known exactly where researchers see that there is potential for these waste materials to come from materials that are not allowed (haram) in Islam to be used as goods that can be used for people's daily life. Then the author uses a type of qualitative research with a descriptive analysis case study approach, with a normative approach to Islamic sharia, while in the discussion the ushul fiqh approach is used, namely istidlal qiyasi. The results of this study indicate that the beneficial value of using waste materials as cement-making materials as a result of the case study approach and normative Islamic sharia, in ushul fiqh istidlal qiyasi is both beneficial, lawful and beneficial because it undergoes a heating process at a high process temperature of 1400 degrees Celsius so that based on the opinion of Islamic scholars of the Hanafi school of thought, the blazing sun can purify soil that is exposed to uncleanness if it is dried in the sun until it loses its color and unclean smell. "The land that has dried up, then the land has been holy." (HR. Zaila'i).